The ABCD of portal vein thrombosis: a systematic approach - Minoda,Alexandre Makoto (2020)
Abstract Portal vein thrombosis refers to complete or partial obstruction of the portal venous system, in the intrahepatic or extrahepatic venous tract or even in the splenic or superior mesenteric veins. This common and potentially fatal condition can develop in various clinical contexts, especially those of liver cirrhosis, hepatocellular carcinoma, and other solid tumors. Certain characteristics, such as the time since the onset of the thrombus (acute or chronic), its biology (hematic or tumoral), the presence of collateral vessels, and the magnetic resonance imaging aspects, are important components of a thorough, careful analysis, as well as informing decisions regarding the appropriate therapeutic strategy. Here, we present a brief review of the anatomy of the portal venous system and a systematic approach to analyzing the condition, using a mnemonic (ABCD, for age, biology, collaterals, and diffusion). We discuss the various imaging methods and illustrate our discussion with images selected from the case files archived at our facility.